Effect of explant density and volume of cultivation medium on in-vitro multiplication of blueberry (Vaccinium corymbosum L.) varieties "Brigitta" and "Legacy" - Rodríguez Beraud, Mario (2015)
The objective of the investigation was to evaluate the in-vitro multiplication of two varieties of blueberry (Vaccinium corymbosum L.), "Brigitta" and "Legacy" in response to five explants densities (5, 10, 15, 20 and 25) and four flask volumes (10, 20, 30 and 40 mL) for cultivation. For both varieties the cultivation medium WPM (Woody Plant Medium) was used. The experiment was completely randomized with 20 treatments and 12 repetitions per treatment. After 45 days of cultivation we evaluated the height of shoots, number of shoots/explant, number of nodes/shoot and number of shoots/flask. Variety "Brigitta" had highest shoots at higher densities and flask volumes, while variety "Legacy" had the highest average shoot height with intermediate densities and high volumes. Regarding the number of shoots/explant, the volume of the medium had no influence on "Brigitta", however, higher plant densities affected this parameter. With variety "Legacy" the maximum number of shoots was achieved with lower plant densities and intermediate culture volumes per flask. In relation to the number of nodes per explant "Brigitta had lower numbers as compared to "Legacy", but with both varieties the number of nodes decresed with smaller volumes of medium in the flasks. For the number of shoots per flask, "Brigitta" responsed best at higher densities exceeding 40 shoots per flask. In contrast, "Legacy" produced maximum results at density of 25 explants in 30 mL of medium. It is concluded that for the optimum multiplication of both varieties the correct selection of both, the planting density and the volume of multiplication medium are important.